Analisis Penerapan PSAK 24 Tentang Imbalan Kerja Pada PT Sinar Kencana Tech - Gumilar, Yana; Purwanti, Meilani (CV. ITTC INDONESIA, 2024)
This research aims to determine the application of PSAK 24 regarding employee benefits at PT Sinar Kencana Tech. This research method is a qualitative descriptive method, namely this research was carried out by conducting interviews, observation and documentation techniques with PT Sinar Kencana Tech employees who can provide additional information and data that may be needed in this research. So that it provides a clear enough picture to analyze and compare with existing theory according to PSAK 24 and its application at PT Sinar Kencana Tech. The data used is primary data in the form of direct interviews with the director of PT Sinar Kecana Tech. After conducting the analysis, the research results show that PT Sinar Kencana Tech has implemented measurement, recognition and disclosure in terms of salary provision, annual leave and paid sick leave, profit sharing and bonuses, post-employment benefits, defined contribution programs, and appropriate long service awards. with PSAK 24, but PT Sinar Kencana Tech has not implemented measurement, recognition and disclosure of non-monetary benefits, post-employment benefits (post-employment life insurance and postemployment service facilities), defined benefit programs, paid long-term absences such as long-term leave or leave sabbatical, permanent disability benefits and deferred remuneration.